Social Construction of the Reality of MSME Actors in KSBI Jakarta Regarding President Prabowo’s Free Food Program - Made Wilantara; Misnan; Novianty Elizabeth Ayuna; Ajeng Iva Dwi Febriana (Journal of Advanced Research in Social Sciences and Humanities, 2025)
Aim: To analyze how Micro, Small, and Medium Enterprises (MSMEs) members of the Komunitas Sukses Berjamaah Indonesia (KSBI) Jakarta form their social construction of the free meal program initiated by President Prabowo. Methodology: Using a descriptive qualitative approach based on the social construction theory of Peter L. Berger and Thomas Luckmann, this study describes how the reality of the national program is interpreted, understood, and responded to by MSMEs in the context of the local community economy. The current research adopted situational analysis, literature studies, and observations of community narratives and approaches. Findings: It was found that MSMEs view the free meal program not just as a food policy but as an economic opportunity, a symbol of the state’s concern for the common people, and an accessibility challenge. This social construction is formed through three main stages: externalization in the form of a narrative of expectations for participation in procurement; objectivation through the dissemination of opinions and discussions in the KSBI forum, and internalization in the form of a collective attitude towards the potential for empowerment or exclusion. This study concludes that the meaning of the free meal program is greatly influenced by economic experience, closeness to government networks, and the community’s existence as a space for articulating shared meaning. Implications/Novel Contribution: The study bring unique policy directions for governments and administrators by understanding this social construction, the government and stakeholders can design a more inclusive approach to involving local MSMEs in national-scale programs.